Phosphorus Leaching From Naturally Structured Forest Soils Is More Affected by Soil Properties Than by Drying and Rewetting - Gerhard, Lukas; Puhlmann, Heike; Vogt, Margret; Luster, Jörg (Frontiers in Forests and Global Change, 2021)
Foliar phosphorus (P) concentrations in beech trees are decreasing in Europe, potentially leading to reductions in the trees’ growth and vitality. In the course of climate change, drying and rewetting (DRW) cycles in forest soils are expected to intensify. As a consequence, P leakage from the root zone may increase due to temporarily enhanced organic matter mineralization. We addressed the questions whether sites with different soil properties, including P pools, differ in their susceptibility to DRW-induced P leaching, and whether this is affected by the DRW intensity. A greenhouse experiment was conducted on naturally structured soil columns with beech saplings from three sites representing a gradient of soil P availability. Four DRW cycles were conducted by air-drying and irrigating the soils over 4 hours (fast rewetting) or 48 hours (slow rewetting). Leachates below the soil columns were analyzed for total P, and molybdate reactive P (considered as inorganic P). The difference was considered to represent organically bound P. Boosted regression trees were used to examine the effects of DRW and soil characteristics on P leaching. Contrary to a first hypothesis, that P leaching increases upon rewetting with the intensity of the preceding desiccation phase, intense soil drying (to pF 3.5 to 4.5) did not generally increase P leakage compared to moderate drying (to pF 2 to 3). However, we observed increased inorganic P concentrations and decreased organic P concentrations in leachates after drying to matric potentials above pF 4. Also against our expectations, fast rewetting did not lead to higher leakage of P than slow rewetting. However, the results confirmed our third hypothesis that the site poorest in P, where P recycling is mainly limited to the humus layer and the uppermost mineral soil, lost considerably more P during DRW than the other two sites. The results of our experiment with naturally structured soils imply that intensified drying and rewetting cycles, as predicted by climate-change scenarios, may not per se lead to increased P leaching from forest soils. Soil properties such as soil organic carbon content and texture appear to be more important predictors of P losses.